Do coronavirus vaccine challenge trials have a distinctive generalisability problem?. Issue 9 (7th June 2021) - Eyal, Nir; Gerhard, Tobias
Abstract : Notwithstanding the success of conventional field trials for vaccines against COVID-19, human challenge trials (HCTs) that could obtain more information about these and about other vaccines and further strategies against it are about to start in the UK. One critique of COVID-19 HCTs is their distinct paucity of information on crucial population groups. For safety reasons, these HCTs will exclude candidate participants of advanced age or with comorbidities that worsen COVID-19, yet a vaccine should (perhaps especially) protect such populations. We turn this cliché on its head. The truth is that either an HCT or a field trial has intrinsic generalisability limitations, that an HCT can expedite protection of high-risk participants even without challenging them with the virus, and that an important route to obtaining results generalisable to high-risk groups under either strategy is facilitated by HCTs.